A module centered on the transcription factor Msn2 from arbuscular mycorrhizal fungus Rhizophagus irregularis regulates drought stress tolerance in the host plant - Fan, Xiaoning (The New phytologist, 2023)
© 2023 The Authors. New Phytologist © 2023 New Phytologist Foundation.